Goat kids rearing with cow’s milk in a Győr-Moson-Sopron county farm - Balázs, Orsolya; Némethné Biacsics, Edit; Gulyás, László; Hegyi, Judit (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
Goat breeding is one of the most dynamic developing sector of animal breeding. In the Europian Union the world’s goat herd is found only 1.6%. At the same time 13.2% of the world’s annual goat milk production are produced here. In general european goat breeding is specialized in milk production much rather than the other developing countries. The european milk goat breeding has been so important criterion that realizable amount of mothers’ milk could be increased. So it can be achieved the certificial foster kids methods. This system is already current in Europe and the overseas countries but in Hungary it isn’t general yet. The artificial kid rearing is happening mainly milk replacer formulas in Europe and in other parts of the world. Furthermore the possible solution will be referenced the kid rearing with cow’s milk. We conducted an experiment with cow’s milk to kid rearing in a Győr-Moson-Sopron country. We are included in a control group which is contained bred goat milk kids.
Keywords: goat kid; rearing; cow's milk